2013
DOI: 10.3390/ijms140712978
|View full text |Cite
|
Sign up to set email alerts
|

Achillea millefolium L. Essential Oil Inhibits LPS-Induced Oxidative Stress and Nitric Oxide Production in RAW 264.7 Macrophages

Abstract: Achillea millefolium L. is a member of the Asteraceae family and has been used in folk medicine in many countries. In this study, 19 compounds in A. millefolium essential oil (AM-EO) have been identified; the major components are artemisia ketone (14.92%), camphor (11.64%), linalyl acetate (11.51%) and 1,8-cineole (10.15%). AM-EO can suppress the inflammatory responses of lipopolysaccharides (LPS)-stimulated RAW 264.7 macrophages, including decreased levels of cellular nitric oxide (NO) and superoxide anion pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 48 publications
3
30
1
1
Order By: Relevance
“…As MDA and GSH are critical indicators of oxidative stress, these were measured in LPS-challenged macrophages to determine oxidative stress and to assess the anti-oxidative activity of equol. The results found here are consistent with others' findings that MDA contents increase with LPS induction [3,[32][33][34]. The present work demonstrates successful construction of an oxidative stress model with LPS in chicken macrophages; previous emphasis on LPS-challenged macrophages has been on immune responses.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…As MDA and GSH are critical indicators of oxidative stress, these were measured in LPS-challenged macrophages to determine oxidative stress and to assess the anti-oxidative activity of equol. The results found here are consistent with others' findings that MDA contents increase with LPS induction [3,[32][33][34]. The present work demonstrates successful construction of an oxidative stress model with LPS in chicken macrophages; previous emphasis on LPS-challenged macrophages has been on immune responses.…”
Section: Discussionsupporting
confidence: 82%
“…The contents of cytokines, measured here at 24 h after LPS, were the same as those in control cells or were even lower in the case of TNFα. The contents of cytokines such as TNFα [3,45] and IL-1β [46,47] increased when oxidative stress occurred. The present results demonstrated that oxidative stress still existed at 24 h, despite the lack of increase in cytokines but their levels, and that of TLR4, were increased in the presence of equol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prepared cells were treated with different concentrations of theophylline, hesperetin, arbutin and rottlerin for 24 h. Subsequently, 100 L (0.5 mg/mL) of MTT solution was added to cells, which were then incubated at 37 • C for 30 min and washed twice with PBS. Finally, the cells were lysed with 100 L DMSO, and the absorbance was measured spectrophotometrically at 540 nm using an ELISA reader [21].…”
Section: Mtt Assay For Cell Viabilitymentioning
confidence: 99%